Nitric Oxide: From Research to Therapeutics - Ray, Arunabha; Gulati, Kavita (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book entitled "Nitric Oxide: From Research to Therapeutics" includes the most recent information about the role of Nitric Oxide (NO) in physiology, pathophysiology and its translation to therapeutics. The Editors are vastly experienced in the field of NO research. The international panels of contributors to the various chapters of the book are all well-established researchers and health professionals who have worked in different areas of NO physiology and pathophysiology, and have made a considerable impact in the field. The book is a comprehensive collection of the most recent information on NO as a physiological regulator and its diverse potential as a therapeutic target for the treatment for a variety of disease states. This compilation is aimed at professionals and students from both academia and the industry in the areas of basic biomedical and clinical sciences.
Translating Nitric Oxide Research to therapeutics: a critical appraisal -- Nitric oxide and cardiovascular health -- Nitric oxide and cardiovascular diseases: Cardioprotection, Complications and Therapeutics -- Nitric Oxide and the Heart Autonomic Nervous System -- Exercise induced NO modulation in prevention and treatment of cardiovascular diseases -- Nitric Oxide and Cardio-renal Syndrome -- Nitric Oxide-cGMP-PKG Signaling in the Cardioprotective Effect of cGMP Specific Phosphodiesterase 5 Inhibitors -- Role of Nitric Oxide Synthases in Doxorubicin-Induced Cardiomyopathy -- Role of Nitric Oxide Synthase and Nitric Oxide Signaling in the Neutrophil Ontogeny and Functions -- Cell Death- NO-today: Effect of NO and RNS on non-apoptotic regulated cell death -- Involvement of nitric oxide in insulin secretion to carbohydrate metabolism -- Nitric Oxide : a diagnostic tool and therapeutic strategy in Respiratory Diseases -- Therapeutic potential of nitric oxide in the management of COVID-19 induced Acute Respiratory Distress Syndrome(ARDS) -- Emerging Novel Therapies for COVID-19: Implications for the Use of Nitric Oxide as Anti-COVID-19 Therapy -- Sex differences in stress and stress related neuropsychiatric disorders: Focus on nitric oxide -- Nitric oxide in major depressive disorder -- Role of Nitric Oxide in Alzheimer`s Disease : Perspectives and Trends -- Nitric oxide in Parkinson's Disease: Insights into research and therapeutics -- Stable gastric pentadecapeptide BPC 157 and NO-system -- Exploring the gastroprotective, ulcer healing and chemopreventive properties of nitric oxide-releasing nonsteroidal anti-inflammatory drugs -- The role of nitric oxide in the etiopathogenesis of pre-eclampsia -- Therapeutic Prospects of Nitric Oxide as an Anti-Teratogen -- Ruthenium Nitrosyl Complexes: Photoinduced Delivery of NO to Different Biological Targets -- Nitric Oxide regulation in Microparticle.
Keywords: Human physiology; Neurophysiology; Immunology; Cancer; Cardiovascular system; Physiology; Human Physiology; Neurophysiology; Immunology; Cancer Biology; Cardiovascular Physiology